THE INFLUENCE OF MINERAL FERTILIZER RATE AND PROPORTIONS ON THE DEVELOPMENT PERIOD OF MUSHROOM PLANT (Лучшие интеллектуальные исследования, 2025)
Abstract. This article studies the effect of mineral fertilizer rates and their ratios on different stages of development of mung bean (Vigna radiata). The study analyzes the effect of optimal amounts of basic fertilizers such as nitrogen, phosphorus and potassium and their ratios on the vegetative growth, flowering and fruit setting stages of mung bean. Also, physiological changes observed as a result of increasing or decreasing the rate of fertilizers, differences in yield and quality are determined. The article offers scientific and practical recommendations aimed at forming an effective fertilization system in mung bean cultivation, improving agrotechnical measures and ensuring environmental sustainability.Абстрактный. В статье изучается влияние норм внесения минеральных удобрений и их соотношений на различные фазы развития растений вигны лучистой (Vigna radiata). В исследовании анализируется влияние оптимального количества основных удобрений, таких как азот, фосфор и калий, а также их соотношений на вегетативный рост, цветение и стадии завязывания плодов маша. Он также выявляет физиологические изменения, урожайность и различия в качестве, наблюдаемые в результате увеличения или уменьшения норм удобрений. В статье даны научно-практические рекомендatsiи, направленные на формирование эффективной системы удобрения при возделывании маша, совершенствование агротехнических мероприятий и обеспечение экологической устойчивости.